Entropy-weighted ANP fuzzy comprehensive evaluation of interim product production schemes in one-of-a-kind production. (October 2016) - Mei, Ying; Ye, Jiawei; Zeng, Zhigang
Highlights: Analyze the multi-criteria decision making problem in OKP. Provide an influence factor system for optimizing interim product production scheme. Propose the entropy-weighted ANP fuzzy comprehensive evaluation method. Case study in shipbuilding. Abstract: Most one-of-a-kind production (OKP) products are complex-shaped structural components, where there are only few identical OKP interim products in the same batch. OKP flexible interim product production has the nature of multi-criteria production; the multi-criteria production characteristics correspond to different manufacturing technologies and methods. How to reasonably and effectively determine group/batch production schemes of OKP interim products has become a key strategic consideration in OKP enterprises' multi-criteria production decisions. The primary problem of the current multi-criteria evaluation method is how to judge the matrix scale and determine the weight set, which primarily depends on the rich experience of relevant specialists. These subjective decisions make the evaluation results prone to disagreements. To comprehensively and scientifically evaluate the production processes influenced by the complicated factors in OKP, we establish an influence factor system and present a method that combines subjective and objective weights based on entropy and an analytic network process (ANP). The method avoids a multifarious optimizing process. In addition, this is a novel attempt to use fuzzy comprehensive evaluation based on ANP in production scheme optimization, which to an extent, enriches process optimization methods in manufacturing. Through case studies, we demonstrate our methods feasibility and rationality. The improved evaluation result provides support for multi-criteria production decisions of interim products in OKP.